VD_FINDINFO ML / 2011 / 275 vom 23. Juni 2011 - VD Tribunal cantonal (2011)
MAINLEVÉE PROVISOIRE, BAIL À LOYER, DÉFAUT DE LA CHOSE, RÉDUCTIONEN GÉNÉRAL | 102 al. 1 CO, 104 CO, 259d CO, 259e CO, 259g CO, 82 al. 1 LP